(untitled) (REMUNOM, 2025)
The emergence of cyberculture and the expansion of Digital Information and Communication Technologies (DICTs) have directly impacted educational processes, demanding pedagogical practices that establish dialogue among physical, conceptual, and digital spaces. This study analyzes the potential of a Didactic Sequence (DS) model for teaching Geography in the final years of elementary education, grounded in the intentional and critical use of digital resources such as Learning Objects, Interactive Simulations, Augmented Reality (AR), Virtual Reality (VR), and gamification platforms such as Kahoot!. It is based on the premise that these tools, when integrated into participatory methodologies, can overcome fragmented and traditional teaching approaches, fostering more contextualized, meaningful, and inquiry-based learning. The proposed activities address topics such as Earth’s layers, tectonic plates, volcanism, earthquakes, tsunamis, and ocean currents, in alignment with the Brazilian National Common Curricular Base (BNCC). The proposals involve the use of digital platforms, particularly Sketchfab, which enables the exploration of 3D models, and Kahoot!, which supports gamified diagnostic assessment. By articulating DICTs with socio-interactionist principles, the DS contributes to the development of spatial thinking, enhances student engagement, and strengthens teacher mediation. However, challenges such as the lack of technological infrastructure and the insufficient training of teachers still limit the full implementation of this approach. It is concluded that the integration of digital resources into Geography teaching constitutes a promising strategy for pedagogical innovation and for the construction of an inclusive and high-quality education.